2017
DOI: 10.1111/jrh.12273
|View full text |Cite
|
Sign up to set email alerts
|

Financial and Health Barriers and Caregiving‐Related Difficulties Among Rural and Urban Caregivers

Abstract: Informal caregivers, particularly in rural areas, face financial barriers. Rural caregivers were less likely than urban caregivers to report caregiving-related difficulties. Rural caregivers' coping strategies or skills in identifying informal supports may explain this difference, but additional research is needed to explore this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 32 publications
3
30
1
Order By: Relevance
“…In spite of this, rural caregivers perceive and report fewer caregiving challenges than their urban counterparts ( Brazil et al., 2014 ). Urban caregivers, in contrast, are more likely to report caregiving challenges of the emotional type ( Bouldin et al., 2017 ; Ehrlich, Bostrom, Mazaheri, Heikkila, & Emami, 2015 ). The reason suggested is that rural caregivers may be more emotionally self-reliant ( Easter Seals and National Alliance for Caregiving, 2006 ) and thus better able to use “approach-based” coping strategies such as positive reframing, seeking social support, and problem-solving (O'Connell, Germaine, Burton, Stewart, & Morgan, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of this, rural caregivers perceive and report fewer caregiving challenges than their urban counterparts ( Brazil et al., 2014 ). Urban caregivers, in contrast, are more likely to report caregiving challenges of the emotional type ( Bouldin et al., 2017 ; Ehrlich, Bostrom, Mazaheri, Heikkila, & Emami, 2015 ). The reason suggested is that rural caregivers may be more emotionally self-reliant ( Easter Seals and National Alliance for Caregiving, 2006 ) and thus better able to use “approach-based” coping strategies such as positive reframing, seeking social support, and problem-solving (O'Connell, Germaine, Burton, Stewart, & Morgan, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The burden is largely attributed to the numerous unmet needs and barriers that informal caregivers encounter ( Bee, Barnes, & Luker, 2009 ; Clayton, Butow, & Tattersall, 2005 ; Hudson, Aranda, & Kristjanson, 2004 ; Lafortune, Huson, Santi, & Stolee, 2015 ; Tallman, Greenwald, Reidenouer, & Pantel, 2012 ). Two types of needs—“instrumental” and “emotional”—have been frequently reported in studies of informal caregivers in home care settings, across urban and rural populations ( Bouldin, Shaull, Andresen, Edwards, & McGuire, 2017 ; Brazil, Kaasalainen, Williams, & Dumont, 2014 ). A subset labeled “informational” needs was paramount to family caregivers of adults with acquired brain injury ( Gan, Gargaro, Brandys, Gerber, & Boschen, 2010 ; Longacre, Galloway, Parvanta, & Fang, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This consistent finding has led to efforts to quantify the cost associated with informal care by families and to consider providing employee benefits or government subsidies to support family caregiving, especially for women who leave employment to care for parents who need care. 35,36,37 In relation to an age issue, the finding in this study revealed that about one third of the participants aged 60 years old and older. Although some previous study 38 found that the more advanced age, the more mature and experienced people have in care providing skills.…”
Section: Discussionmentioning
confidence: 69%
“…Scholarship is clear in demonstrating burdens that accrue to caregivers, as evidenced by individual studies and meta‐analyses highlighting poorer physical and psychological health (e.g., Bidwell, Lyons, and Lee 2017; Pinquart and Sörensen 2003, 2007). As they negotiate the complexities of providing care, rural caregivers face additional challenges of less social support, greater isolation, fewer financial resources, more limited access to workplace supports, and barriers to accessing formal services (Bouldin et al 2018; Egdell et al 2010; Ehrlich, Boström, Mazaheri, and Heikkilä 2015; Henning‐Smith and Lahr 2019; Kaufman, Kosberg, Leeper, and Tang 2010) that are unevenly developed across geographic spaces (Herron, Rosenberg, and Skinner 2016). Compared to their urban counterparts, rural caregivers report lower self‐rated health (Crouch, Probst, and Bennett 2017).…”
mentioning
confidence: 99%